THE EFFECT OF DEMOCRACY, CORRUPTION AND UNEMPLOYMENT ON ECONOMIC GROWTH IN 5 ASEAN COUNTRIES - Adib (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Economic growth in developing countries is influenced by the quality of governance, particularly democracy, corruption, and unemployment. This study aims to analyze the effects of these three variables on economic growth in five middle-income ASEAN countries over the period 2011–2024. The research employs descriptive and associative approaches using annual panel data that include economic growth, democracy index, corruption levels, and unemployment rates. The analysis is conducted to assess the relationships and the extent of influence exerted by each independent variable on the dependent variable. The findings reveal that democracy has a positive and significant impact on economic growth, indicating that political stability, accountability, and policy transparency contribute to fostering economic activity. Meanwhile, corruption shows a positive but insignificant effect, suggesting that although corruption may appear to facilitate bureaucratic processes in certain conditions, it does not provide substantial benefits to economic growth. Unemployment exhibits a negative yet insignificant influence, implying that its impact on growth is not always direct and may vary depending on the labor market structure of each country. Overall, the results highlight the importance of strengthening democratic institutions as a key driver of economic growth in the ASEAN region.